Variability in the management of line-related upper extremity deep vein thrombosis. (September 2019) - Cires-Drouet, Rafael; Sharma, Jashank; McDonald, Tara; Sorkin, John D; Lal, Brajesh K
Objectives: Central-venous devices are risk-factors for upper extremity deep vein thrombosis. We surveyed physicians to identify practice-patterns and adherence to American College of Chest Physicians guidelines. Methods: The 13-question survey obtained physician-demographics and treatment-choices. Respondents were grouped into surgical and medical specialists. Data were reported as ratios and percentages, and compared using Fisher's exact test. Results: We received 143 responses from physicians; 65% treated one-to-two new cases/month. Most physicians (69.2%) used anticoagulation; 36.4% retained the catheter and 32.9% removed it. Medical-specialists retained catheters more often than surgeons ( p  = 0.027). For recurrences, 84% repeated anticoagulation; 50.3% retained the catheter. A majority anticoagulated upper-extremity deep-vein thrombosis in long-term catheters for three months only (55.1%). Direct oral anticoagulants were used frequently (43.6%). Only 10% believed that existing guidelines were appropriate and only 2.8% followed all guidelines. Conclusion: There is great variability in treatment-decisions for upper-extremity deep-vein thrombosis. The existing guidelines are considered inadequate and not followed by most physicians.